Influence of Pelvic Intensity-Modulated Radiation Therapy With Concurrent Cisplatin-Based Chemotherapy of Cervical Cancer on the Vaginal Microbiome - Jiang, Li; Li, Bo; Zhang, Yong; Ma, Shanshan; Liu, Chang; Liang, Feifei; Wei, Zhuxin; Huang, Tingting; Wang, Rensheng (Frontiers in Oncology, 2021)
Pelvic intensity-modulated radiation therapy (IMRT) combined with concurrent chemotherapy is an effective treatment for cervical cancer; however, radiation resistance impairs its clinical benefit. The vaginal microbiome plays an important but poorly understood role in cancer radiochemotherapy. In this study, we investigated the effects of treatment on the overall composition and alteration of the vaginal microbiome in patients receiving pelvic IMRT with concurrent cisplatin-based chemotherapy. We collected samples from twenty patients with cervical cancer and six healthy controls and performed 16S rRNA sequencing. Vaginal microbial composition analysis revealed significant differences between the two groups, but no significant differences between radiation treatment time points. However, the relative abundances of Gammaproteobacteria, Gemmatimonadetes, Gemmatimonadales, Pseudomonadales, Gemmatimonadaceae, Rikenellaceae, Acinetobacter, Desulfovibrio, Prevotella 9, Rikenellaceae RC9 gut group, Turicibacter, and the metagenome increased with time. The results encourage further study into the effects of the vaginal microbiome on cervical cancer treatment strategies, especially radiochemotherapy. Better understanding of these effects could inform new therapeutic approaches to enhance the efficacy of radiochemotherapy.